Algebra II for Dummies - Sterling, Mary Jane (NJ: Jhon Wiley & Sons, Inc., 2015)
Algebra can evoke anxiety in the best of us. Sterling shows you how to get up to speed on exponential functions, conic sections, matrices, and other advanced concepts.
Going beyond beginning algebra -- Toeing the straight line: linear equations -- Conquering quadratic equations -- Rooting out the rational, radical, and negative -- Graphing your way to the good life -- Formulating function facts -- Sketching and interpreting quadratic functions -- Staying ahead of the curves: polynomials -- Reasoning with rational functions -- Exposing exponential and logarithmic functions -- Cutting up conic sections -- Solving systems of linear equations -- Solving systems of nonlinear equations and inequalities -- Simplifying complex numbers in a complex world -- Making moves with matrices -- Making a list: sequences and series -- Everything you wanted to know about sets -- Ten multiplication tricks -- Ten special types of numbers.
Includes index.
Keywords: Algebra; Algebra. -- ME